Comparison of ultrasound⁃guided nerve block and local infiltration analgesia on analgesic effect in patients with laparoscopic cholecystectomy - LIAO Yongfeng，WANG Hui，ZHANG Yuedong (Zhongguo linchuang yanjiu)
Objective To compare the influence of ultrasound⁃ guided nerve block and local infiltration analgesia on analgesic effect and levels of stress markers in patients undergoing laparoscopic cholecystectomy（LC），and to establish a theoretical foundation for optimizing clinical selection of postoperative pain management approaches. Methods A total of 76 patients undergoing elective LC in Anqing First People's Hospital of Anhui Medical University from January 2020 to November 2024 were selected prospectively and divided into group A（ultrasound⁃guided nerve block analgesia after anesthesia induction，n=38）and group B（local infiltration analgesia after the end of surgery，n=38）by random envelope method. The postoperative indicators，pain status［visual analogue scale（VAS）］，stress response indicators［plasma epinephrine（E），norepinephrine（NE），cortisol（Cor）］and occurrence of adverse reactions were compared between two groups. Results The postoperative awakening time in group A was shorter than that in group B［（12.26±2.17）min vs（20.08±3.34）min，P<0.05］，and the dosage and frequency of additional analgesic drugs were lower than those in group B（P<0.05）. Incision VAS score and non⁃incision VAS score in group A were lower than those in group B at postoperative awakening and at 6，12 and 24 hours after surgery（P<0.05）. At 6 hours after surgery，the levels of E，NE and Cor in the two groups were increased，but the levels in group A were lower than those in group B（P<0.05）. The adverse reactions revealed no statistical differences between group A and group B（10.53% vs 7.89% ，P>0.05）.Conclusion Compared with local infiltration analgesia，ultrasound⁃guided nerve block has a better analgesic effect on LC patients，and the latter one can shorten the postoperative awakening time more effectively，reduce the dosage and frequency of postoperative analgesic drugs，relieve the degree of postoperative pain，and reduce the stress response without aggravating adverse reactions.